Knee Cartilage Composition, Morphology, and Function in Asymptomatic Recreational Runners, Non-Runners, and Obese Adults: A Matched 4HAIE MRI Study - Lukáš Slovák; Jan Plešek; Lucie Šustková; David Zahradník; Jaroslav Uchytil; Jan Šustek; Jiri Skypala; Jan Urbaczka; Miloš Golián; Miika T. Nieminen; Victor Casula; Daniel Jandačka (Medicine & Science in Sports & Exercise, 2026)
Introduction: Identifying early alterations in asymptomatic individuals with different physical activity levels and/or BMI is essential for understanding joint health before clinical symptoms develop. Purpose: The aim of this study was to compare cartilage composition, morphology, and subjective knee function among age- and sex-matched recreational runners (R), non-runners (NR), and obese individuals with BMI ≥ 30 kg/m²) (O). Methods: This cross-sectional study included 183 asymptomatic adults (61 age- and sex-matched triplets: R, NR, O), aged 18–65 years, from the 4HAIE cohort, with an average age difference of 214 ± 87 days within triplets. MRI (1.5 Tesla) was used to quantify T2 relaxation times and assess morphology (Normal vs. Abnormal/Degenerated) across 12 femorotibial regions. Knee function was evaluated with the KOOS questionnaire. Group differences were tested using non-parametric statistics. Cartilage morphology was further examined by binary logistic regression. Results: Runners showed significantly higher T2 values in several lateral femoral and tibial regions compared with NR and O (p < 0.05). Obese had a lower prevalence of normal cartilage in the medial central tibia (O: 75.4% vs. R: 91.8% vs. NR: 93.4%) and up to fourfold higher odds of abnormal findings (R/O: OR = 3.65, 95% CI: 1.30–10.23; NR/O: OR = 4.65, 95% CI: 1.44–14.92). KOOS scores were lowest in obese, particularly for Activities of Daily Living ( p = 0.004). No significant differences in morphology or function were observed between runners and non-runners. Conclusions: Obesity (BMI ≥ 30 kg/m²) was associated with a higher prevalence of cartilage abnormalities and poorer self-reported function in activities of daily living, whereas recreational running was not linked to structural or functional impairment.